Analysis of source contribution to pass-by noise for a moving high-speed train based on microphone array measurement. (April 2021) - Li, Muxiao; Zhong, Shuoqiao; Deng, Tiesong; Zhu, Ziwei; Sheng, Xiaozhen
Highlights: Noise source areas defined for moving train. Sound power estimated from microphone array data for each area as moving monopole source. Pressure spectra generated by all sources added incoherently to predict train pass-by noise. Predicted pass-by noise compared to measurement with good agreement. Contributions to pass-by noise of various sources predicted. Abstract: Microphone array measurement processed using the delay-and-sum beam-forming and de-convolution techniques is commonly performed to identify and quantity noise sources on a moving train. Results from such a measurement may be employed to analyse contributions of the sources to pass-by noise of the train, proving directions for pass-by noise control and reduction. In order to carry out such an analysis, a source contribution model is developed in this paper. This model is established by assuming that noise sources on the train are incoherent monopole sources, and applying the frequency spectrum generated by a harmonic monopole source moving uniformly in a free-space. The model is validated against a set of measurements for a high-speed train running along a track on viaduct at different speeds.